Study of Consistent Characteristics of the Ointment with Octopirox - V. A. Solodovnyk; V. V. Hladyshev; A. P. Lysianska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Effective therapy of seborrheic dermatitis remains an actual task for the dermatological practice. Octopirox has a significant antimycotic activity and a wide spectrum of antibacterial effect both against gram-negative and gram-positive pathogenic microorganisms.